IMF Staff papers : Volume 43 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1996)
This paper examines the role of the labor market in the transmission process of adjustment policies in developing countries. It begins by reviewing the recent evidence regarding the functioning of these markets. It then studies the implications of wage inertia, nominal contracts, labor market segmentation, and impediments to labor mobility for stabilization policies. The effect of labor market reforms on the flexibility of the labor market and the evidence regarding the wage and employment effects of trade reform are discussed next. The last part of the paper identifies a variety of issues that may require further investigation.